The bank lending channel of monetary policy transmission in Vietnam: Impacts of the COVID-19 pandemic and the financial crisis - Minh Thanh Loi; Van Dan Dang (Cogent Business & Management, 2023)
This paper aims to analyze changes in the transmission of monetary policy via bank lending when considering the impact of the COVID-19 pandemic and the financial crisis. Using bank-level data of 31 commercial banks in Vietnam from 2007 to 2021, we provide consistent evidence that the impact of monetary policy on bank lending tends to be more pronounced in the period of the COVID-19 pandemic. Besides, we document that the bank's loan supply is more sensitive to monetary policy adjustments during the global financial crisis. Thus, a general pattern can be detected, i.e. the monetary policy transmission through the bank lending channel is stronger under unfavorable macro contexts in Vietnam. Accordingly, it can be suggested that adjustments in the monetary policy of the central bank have still been effective in periods of macro difficulty and the implementation of unconventional monetary policy in Vietnam is not necessary yet. Regression results when using the sample-splitting technique are consistent with those using interactive variables, providing evidence to confirm the robustness of the findings obtained in the study.
Keywords: G21; E52; 650; monetary policy; COVID-19 pandemic; financial crisis; Bank lending; economic cycle